The prolyl isomerase Pin1 interacts with and downregulates the activity of AMPK leading to induction of tumorigenicity of hepatocarcinoma cells. Issue 10 (30th April 2012) - Khanal, Prem; Kim, Garam; Yun, Hyo Jeong; Cho, Hae‐Guk; Choi, Hong Seok
Abstract : Pin1 is a unique regulator that catalyzes the conversion of a specific phospho‐Ser/Thr‐Pro‐containing motif in target proteins. Herein, we identified AMP‐activated protein kinase (AMPK) as a Pin1‐binding protein. Pin1 wild‐type, but not Pin1 mutant at serine 16 (S16A), associated with AMPK. Reciprocally, the constitutively active form of AMPK (AMPK‐CA), but not the dominant negative form of AMPK (AMPK‐DN), interacted with Pin1 wild type. In addition, mutation of Ser176 site in AMPK led to a significant loss of binding between AMPK and Pin1. Ablation of the Pin1 gene in MEFs enhanced AMPK phosphorylation induced by AICAR. Pin1 overexpression in Pin1 −/− MEFs and SK‐HEP‐1 cells attenuated AMPK phosphorylation induced by EGF, whereas gene knockdown of Pin1 by siRNA enhanced it. The association between Pin1 and AMPK was increased by EGF, leading to their interaction with protein phosphatase‐2A (PP2A). Furthermore, Pin1 increased the PP2A activity induced by EGF. In addition, AMPK‐WT and AMPK‐CA, but not AMPK‐DN, inhibited EGF‐induced neoplastic cell transformation of JB6 Cl41 cells and tumorigenicity of SK‐HEP‐1 cells. The overexpression of Pin1 in JB6 Cl41 cells and SK‐HEP‐1 cells attenuated the inhibitory effect of AMPK in EGF‐induced neoplastic cell transformation of JB6 Cl41 and tumorigenicity of SK‐HEP‐1 cells, respectively. Taken together, these results indicate that Pin1 plays a pivotal role in EGF‐induced carcinogenesis through downregulation of AMPK activity in hepatocarcinoma cells. © 2012 Wiley Periodicals, Inc.